Vowels and consonants in Arabic - Harianto, Neldi; Habibi, Nicolas; Malik, Khairil; Sholiha, Mar’atun (Proceeding International Conference on Malay Identity, 2023)
Phonology, including a new branch of knowledge in Arabic. This science was born from the adaptation of Tajweed Science. For those who want to know Arabic, it is important to know that almost half of the Arabic phonemes are unknown or have no equivalent in Indonesian. Arabic has 28 alphabets, all of which are consonants. Vowels in Arabic writing are three punctuation marks called syakl such as Fathah, Kasrah and Dhammah. When the Arabic alphabet is called a vowel, it is when the letters Alif through Yaa are added with Harakat, both the Harakat Fathah (?), Kasrah (?) and Dhammah (?). This is different from Indonesian which has a vowel alphabet in letter form, namely A, I, U, E, and O and the rest are consonants